THE EFFECT OF SPONSORSHIP EVENT AND PUBLICITY ON CONSUMER BUYING BEHAVIOR AT PT. SINAR GALESONG MANADO - Dawali, Achmad Dimas; Pandowo, Merinda (Universitas Sam Ratulangi, 2016)
Companies usually pay attention to promotion of its brand in order to attract consumers, promotion is one of tools that supports marketing part to introduce the products to customers. Various promotional techniques are used by the marketer to influence the consumer decision making. The objectives of the research are to analyze the impact of sponsorship, event, and publicity to consumer buying behavior, partially and simultaneously. The research is quantitative type of research where investigates the impact of sponsorship, event, and publicity to consumer decision making, using a multiple regression model to answer the research problem. Samples were taken by 50 respondents that are PT. Sinar Galesong’s Manado customer. This research conclude that there is a significant effect of event and publicity to consumer buying behavior, and there is a significant effect of sponsorship, event, and publicity simultaneously to consumer buying behavior, whereas sponsorship does not have a significant effect to consumer buying behavior. Company management must be proactive in event activities and also to shows their product in mass media, banner, and other advertising activities. Company management should consider to follow-up all the publicity that already held whether it must be developed or creates the new ones. Keywords: promotional mix, sponsorship, event, publicity